Effects of dietary supplementation with turmeric (Curcuma longa) and ginger (Zingiber officinale) on growth performance and selected biological indices of Nile tilapia (Oreochromis niloticus) - Pham Thi, Dung; Nguyen Phuc, Hung; Duong Thi Anh, Dao; Le Thi, Tuyet; Thi Trung Thu, Nguyen; Thi Bich Ngoc, Nguyen; Ngoc Hoan, Le; Thi Nhu Trang, Do; Nguyen, Thi Hong Hanh (Hue University Journal of Science: Natural Science, 2025)
This study investigated the synergistic effects of combined turmeric (Curcuma longa) and ginger (Zingiber officinale) supplementation on growth performance, feed efficiency, and physiological parameters of Nile tilapia (Oreochromis niloticus), hypothesizing that complementary antioxidant and anti-inflammatory pathways would enhance nutrient utilization and metabolic efficiency. Juvenile fish were fed four experimental diets for 90 days: a control diet and three diets containing combined turmeric and ginger with 1:1 ratio at 0.5% (0.25% turmeric + 0.25% ginger, TG0.5), 1.0% (0.5% turmeric + 0.5% ginger, TG1.0), and 2.0% (1.0% turmeric + 1.0% ginger, TG2.0) total inclusion levels. Growth performance was significantly enhanced with TG0.5 supplementation, achieving 44% higher final body weight (175.18 vs. 121.71 g), 57% greater weight gain (556.13 vs. 354.99%), 24% improved specific growth rate (2.29 vs. 1.84 %/day), and 26% better feed conversion efficiency (1.36 vs. 1.84) compared to the control group. Higher inclusion levels (TG1.0 and TG2.0) showed intermediate improvements without statistical significance. Importantly, no adverse effects were observed on survival rates (95-100%), hematological parameters, or somatic indices, indicating physiological safety across all inclusion levels. These findings demonstrate that moderate supplementation with combined turmeric and ginger (0.5% total, 1:1 ratio) significantly enhances growth performance and feed utilization in Nile tilapia through synergistic mechanisms without compromising fish health, supporting their application as effective natural feed alternatives in sustainable aquaculture systems.